Boycott Movement on Dimensions Literatures - Rahayu, Solihah Sari (Journal of Islamic Economics Literatures, 2025)
This study aims to examine the research development on the topic of "Boycott Movement" and to propose a research agenda based on journals published on this theme. This research employs a qualitative method with a bibliometric analysis approach. The data used is secondary data on the theme of "Boycott Movement" sourced from the Dimension database, comprising 214 journal articles. Subsequently, the data was processed and analyzed using the VosViewer application to map the bibliometric development of "Boycott Movement" research worldwide. The results of the study found 3 clusters with the most frequently used keywords being boycott, movement, study, Israel, state, perspective, world, and society. Furthermore, research path topics related to the Boycott Movement include Consumer behavior in boycott movements, Historical and geopolitical boycott dynamics, and Ethical issues in boycott campaigns.